MEDIA MEDIA EDUKASI INSTAGRAM LIVE STREAMING DALAM UPAYA PEMELIHARAAN KESEHATAN GIGI DAN MULUT - Dian Femala; Riyani A.S.D; Mariyani Y; Suryana Suryana; Halimah Halimah (JURNAL TERAPIS GIGI DAN MULUT, 2026)
Public knowledge about dental and oral health maintenance is still relatively low, although technological developments have opened up new opportunities for health education through social media. One potential platform is Instagram, particularly through its live streaming feature, which allows real-time interaction between educators and audiences. This study aims to determine the knowledge of followers of the @sobatdental_ account before and after education and to analyse the effectiveness of using Instagram Live Streaming in improving knowledge about dental and oral health maintenance. The research design used was a quasi-experimental approach with a one-group pre- test and post-test without a control group. The study sample consisted of 39 respondents who were followers of the @sobatdental_ account and participated in the educational live streaming session. Data were collected through online questionnaires before and after the education session and analysed using the Wilcoxon test. The results showed that before the education session, only a portion of respondents had sufficient knowledge, as evidenced by the scores before the pre-test education session, where only 38.5% had sufficient knowledge. Meanwhile, after the post-test education session, all respondents (100%) had adequate knowledge. The Wilcoxon test showed a significance value of 0.000 (p < 0.05), indicating a significant increase in knowledge.This significant change was due to the interactive delivery of material through the live streaming feature, which allows for direct two-way communication, the use of visual media such as phantoms for hands-on practice, and the concise and easy-to- understand delivery style. This study concludes that the Instagram Live Streaming feature has proven effective as an educational medium in increasing knowledge about dental and oral health maintenance among followers of the @sobatdental_ account. Keywords: Instagram, live streaming, health education, dental and oral health, social media